The Effect of Entrepreneurial Competence and Family Support on the Success of Women's Microenterprises in Sindang Kasih Village - Aina Listiana (Sekolah Tinggi Agama Islam Kuningan, 2025)
Women's micro-enterprises in rural Indonesia play an important role in promoting family economic resilience, but still face various structural and social constraints. Lack of entrepreneurial competence and low family support are two main factors that hinder the success of women's micro-enterprises, especially in Sindang Kasih Village. This study aims to analyze the influence of entrepreneurial competencies and family support on the success of women's micro-enterprises in the region. The method used is a quantitative approach with a causal associative research design. The sampling technique used was a saturated sample technique, with a total of 35 female micro-entrepreneurs as respondents. Data collection was conducted through questionnaires, limited interviews, and documentation, with data analysis using multiple linear regression and classical assumption tests. The results showed that both entrepreneur competence and family support had a positive and significant effect on the success of women's micro businesses partially and simultaneously. The coefficient of determination of 0.629 indicates that the two independent variables explain 62.9% of the variation in business success. This research provides an important contribution to the development of gender and family-based microenterprise empowerment models, and can serve as a reference in designing local policies and training programs that are more contextual and inclusive in the future.